Hubungan Antara Usia Dengan Kelelahan Kerja Pada Tenaga Kesehatan Di Ruang Isolasi Covid-19 RSUD Sayang Rakyat Kota Makassar - Azizah, Nur; Andi Nurlinda; Suharni A. Fachrin (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Work fatigue can reduce performance, increase error rates, and work accidents. Data from the Directorate General of Manpower Supervision Development shows that there are 847 work accidents in Indonesia, 36% of which are due to high levels of work fatigue. One of the problems of work fatigue in healthcare workers is age. The influence of age on work fatigue occurs because of body functions that can affect a person's endurance and work capacity. This study aimed to determine the relationship between age and work fatigue in healthcare workers in the COVID-19 isolation room at the Sayang Rakyat Regional General Hospital (RSUD) in Makassar City. This type of research is quantitative research using the cross-sectional study method with a purposive sampling method with a sample of 54 people. Data were collected using the Chi-square test at a 95% confidence level (α = 0.05). The study showed a relationship between age and work fatigue (p = 0.001). It is hoped that future researchers can analyze the relationship between work fatigue and age factors in healthcare workers at the Sayang Rakyat Regional General Hospital (RSUD) in Makassar City.